Kryteria oceny efektywności bankowych produktów kredytowych - Koszykowski, Marek (The Criteria of Credit Products' Efficiency Evaluation, 2005)
In the paper there are described criteria used to evaluate efficiency of credit products in a bank. There are presented mainly the financial criteria, from earnings to risk adjusted criteria.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 239-248